2018
DOI: 10.1177/1049909118786409
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Characteristics and Lengths of Stay Associated With Acute Palliative Care: A 10-Year National Perspective

Abstract: Patient demographics and characteristics are essential components associated with length of stay in hospice. Race, age, gender, health insurance status, income level, and location of hospice care services are indicators that are associated with differing lengths of stay. Hospice care demand is on the rise, and with 70 million boomers retiring in the next few decades, demand is expected to increase. It is because of demand that exploring the factors that affect a patient's length of stay is essential for unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…On a sociodemographic level, the needs of the seriously ill person with MCC can be influenced by age, gender, socioeconomic status, race, ethnicity, level of income, and level of education. 32 Sociodemographic characteristics have been shown to impact health outcomes, as they can impact access to care or ability to pay for health care and result in disparities related to race, ethnicity, age, or gender. [32][33][34][35] The adapted model accounts for goals, values, or preferences of the individual.…”
Section: Factors Affecting Needs Of the Individualmentioning
confidence: 99%
See 1 more Smart Citation
“…On a sociodemographic level, the needs of the seriously ill person with MCC can be influenced by age, gender, socioeconomic status, race, ethnicity, level of income, and level of education. 32 Sociodemographic characteristics have been shown to impact health outcomes, as they can impact access to care or ability to pay for health care and result in disparities related to race, ethnicity, age, or gender. [32][33][34][35] The adapted model accounts for goals, values, or preferences of the individual.…”
Section: Factors Affecting Needs Of the Individualmentioning
confidence: 99%
“…32 Sociodemographic characteristics have been shown to impact health outcomes, as they can impact access to care or ability to pay for health care and result in disparities related to race, ethnicity, age, or gender. [32][33][34][35] The adapted model accounts for goals, values, or preferences of the individual. 10 Social, cultural, or religious beliefs that influence the needs of a seriously ill person with MCC are also relevant.…”
Section: Factors Affecting Needs Of the Individualmentioning
confidence: 99%
“…1 Prior research has identified sex-based disparities in both the intensity and the frequency of health care services, including hospital admission, access to home-based end-of-life care and use of lifesustaining interventions at the very end of life, accessed by male and female patients. [2][3][4][5] Palliative care improves quality of life, reduces symptom burden, and is associated with a reduction in use of health care services, an increase in quality-adjusted survival and an overall substantial cost-savings among patients with terminal lifelimiting conditions. [6][7][8][9][10][11][12] There remains considerable uncertainty about potential disparities in physician-delivered palliative care between male and female patients at the end of life.…”
mentioning
confidence: 99%